2010
DOI: 10.1007/s00497-010-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Pollen performance of Raphanus sativus (Brassicaceae) declines in response to elevated [CO2]

Abstract: Although increases in atmospheric [CO(2)] are known to affect plant physiology, growth and reproduction, understanding of these effects is limited because most studies of reproductive consequences focus solely on female function. Therefore, we examined the effects of CO(2) enrichment on male function in the annual Raphanus sativus. Pollen donors grown under elevated [CO(2)] initially sired a higher proportion of seeds per fruit than ambient [CO(2)]-grown plants when each was tested against two different standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Pollen number and/or viability are key paternal traits that affect seed set and germination and are highly sensitive to environmental signals. In fact, these traits have been shown to be sensitive to parental e CO 2 (Wang & Griffin, ; Prasad et al ., ; Marshall et al ., ) and, hence, are likely to have mediated some of the germination responses reported here. Male contribution to seed germinability can also result from genetic factors.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Pollen number and/or viability are key paternal traits that affect seed set and germination and are highly sensitive to environmental signals. In fact, these traits have been shown to be sensitive to parental e CO 2 (Wang & Griffin, ; Prasad et al ., ; Marshall et al ., ) and, hence, are likely to have mediated some of the germination responses reported here. Male contribution to seed germinability can also result from genetic factors.…”
Section: Discussionmentioning
confidence: 81%
“…A number of studies have indicated that genotypic (Wulff & Alexander, ; Curtis et al ., ; Ward & Strain, ; Andalo et al ., ; Bai et al ., ) and species‐specific (Farnsworth & Bazzaz, ; Jablonski et al ., ) differences interact with parental CO 2 concentrations to determine reproductive quality and/or outputs. The limited research also suggests that both female (Garbutt & Bazzaz, ; Jablonski et al ., ; Grünzweig, ) and male (Prasad et al ., ; Marshall et al ., ) components of reproductive fitness can be influenced by e CO 2 . However, the relative contribution of maternal vs paternal traits regulating seed germination responses to e CO 2 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was shown that the pollen performance decreased in Raphanus sativus in response to elevated CO 2 levels [53]. Drought stress resulted in a reduction of the pollen viability from approximately 46% to 24% (Additional file 1).…”
Section: Resultsmentioning
confidence: 91%
“…This decrease in pollen viability may have resulted from a nutrient limitation that developed as CO 2 became abundant [79]. Both nitrogen and phosphorous can become limiting under elevated CO 2 [80], and a reduction in their availability can reduce pollen quality [79].…”
Section: Pollenmentioning
confidence: 99%